The Confusing World of Cryptocurrency and Tax Compliance Issues - Crawford, Constance; Crawford, Corinne L.; Vallach, Glenn C. (Journal of Economics and Behavioral Studies, 2022)
Subtitle A, of the Internal Revenue Code (IRC), contains regulatory provisions regarding the federal taxes imposed on the income of both individuals and corporations. The IRC guidance is intended to provide a determination of all income that must be reported on tax returns and potentially could become subject to an income tax. A new form of currency, known as cryptocurrency appeared on mainstream trading platforms beginning in 2009. Bitcoin initially was the most widely recognized digital currency but other virtual currency versions soon followed. Initially, taxpayers mistakenly believed that cryptocurrency transactions were not subject to Subtitle A of the IRC. Therefore, crypto transactions were assumed to be non-taxable and non-reportable for tax purposes. However, within a few years of the introduction of Bitcoin into the US economic system, the Internal Revenue Service (IRS) introduced tax guidance pertaining to cryptocurrency transactions. In 2014, the IRS responded with Notice 2014-21 as the popularity of Bitcoin grew exponentially. The IRC guidance stated that cryptocurrency must be treated as property for federal tax purposes. The tax implication of the IRS guidance was that cryptocurrency transactions would result in either a gain or loss for tax purposes on Schedule D. This guidance resulted in a recognition that all cryptocurrency transactions would be subject to federal income tax.